Development of Encarsia tabacivora (Viggiani) (Hymenoptera: Aphelinidae) in nymphs of Bemisia tabaci (Gennadius) MEAN 1 (Hemiptera: Aleyrodidae) - Gamarra, H.; Sporleder, M.; Supanta, L.; Rodríguez, A.; Kroschel, Jürgen; Kreuze, Jan F. (Cold Spring Harbor Laboratory, 2023)
Encarsia tabacivora Viggiani 1985 (Hymenoptera: Aphelinidae), is an endoparasitoid of whiteflies, including Bemisia tabaci (Gennadius) MEAN 1 (Hemiptera: Aleyrodidae), reported from southern USA, Caribbean, and Brazil. In field surveys, the natural occurrence of E. tabacivora was confirmed in the Cañete valley of Peru. Its biology and development was studied under laboratory conditions at 20°C and 70-75% RH. The results showed that fertilized females lay their eggs inside nymphs of the 3rd and early 4th instar of B. tabaci MEAN 1. The stages of development are egg, three larval instars, prepupa and pupa. Development from egg to adult lasted 19.3 (SE±0.17) days for females. No males were produced, which indicates that E. tabacivora exhibits thelytokous parthenogenesis. Parasitized host nymphs exhibited multiple oviposition punctures and several L1-instar wasps were observed in individual host nymphs, indicating superparasitism. However, from the L2-instar onwards only one individual developed to adult stage. E. tabacivora might be a prospective biological control agent for B. tabaci in sweet potato also for minimizing the spread of whitefly-induced plant viruses in Peru and other regions of the world. The knowledge gained might be helpful in establishing mass rearing protocols of E. tabacivora for inoculative releases.